URGENSI KETELADANAN BAGI SEORANG GURU AGAMA (Kajian Terhadap Metode Pendidikan Islam) - Rodin, Rhoni (STAIN Ponorogo, 2013)
Abstract: Education is a process to humanize human beings. Therefore, the methods employed by the teacher should provide valuable characters since students make the teacher as the central figure in the process of learning. Moreover, the worldâ figures that serve valuable morals for students are currently in crisis. In this void, therefore, the field of education should be triggered by improving the quality of teacherâs performance,especially for the religious teacher. The religious teacher is highly demanded to give valuable characters in all aspects of life. Hence, the educational process is not only to transfer knowledge but also to build moral valuesÂ Â to students. Teacherâs modelingplays a vital role in the teaching-learning process. In accordance to this, the religious teacher also functions as a spiritual father for students who provides knowledge, moral values, and justification. In this case, the teacher requires not only to have adequate pedagogical skills, but also to be able educate students well. This is due to the fact that education is aimed not only to transfer knowledge, but also to build valuable character,that is the teacherâs ability to provide model of valuable attitude and positive values to students.